Determinación de la frecuencia de leptospirosis caprina y de los factores asociados en la parroquia Limones, del cantón Zapotillo - Mora Quezada, Edgar Vicente (2023)
Leptospirosis is a bacterial disease of worldwide distribution that affects both domestic and wild mammals and humans (Peña, 2012). Caprine leptospirosis is prevalent worldwide, with the regular manifestations of the disease including altered fertility, neonatal deaths and abortions, which generate substantial economic losses (Lilenbaum et al., 2008), (Martins et al., 2012); the objectives of this study were to determine the frequency of caprine leptospirosis and the associated factors in Limones parish, Zapotillo canton, we collected fifty blood samples from 10 goat farms between July and August 2022 to analyze blood serum using the Tube Microagglutination Test (TMA) (Fraga et al., 2021), considering a cut-off point ≥ 1:100 for diagnostic interpretation. A panel of 21 serovars of Leptospira interrogans (Canicola, Pomona, Icterohaemorrhagiae, Bratislava, Autumnalis, Pyrogenes, Australis, Sexkoebing, Betaviae, Djesimen, Hebdomedis, Hardjo, Copenhageni, Wolffi, Borincana), (Grippotyphosa) Leptospira Weili (Celledoni), Leptospira Borgpetersewi (Castellonis, Javanica. Tarassovi), Leptospira Santorasai (Shermani) and Leptospira Biflexa (Andamana). Ten per cent of the individuals were seropositive, with the Andamana serovar being the most frequent (4%), followed by the Pomona, Castellonis and Autumnalis serovars (2% each, respectively); we found no antibody detection factors in this study.